2008
DOI: 10.1149/1.2917907
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Wear-Mode Comparison in Copper Electrochemical Mechanical Polishing

Abstract: This paper investigates friction and wear mechanisms of copper electrochemical mechanical polishing ͑ECMP͒ in pH and potential parameters as illustrated in the Pourbaix diagram. Three approaches were used in this study. First, a unique experimental setup was designed to investigate the effects of pH and electropotential on planarization. Second, the friction was measured in situ during polishing and used as a monitoring process. Third, the worn areas correlated with the frictional behavior of post-chemical mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…If there is high friction on the Cu reaction layer, Cu removal rate would be higher. [9][10][11] Table II shows a summary of slurry characteristics and Table III shows various Cu slurry performances (Slurry A, B, and C) for low, middle, and high-speed Cu removal rates. First of all, the friction for the Cu reaction layers of those slurries is measured using a conventional friction force microscope (FFM), revealing that the friction of high-speed slurry is not the highest of all the slurries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is high friction on the Cu reaction layer, Cu removal rate would be higher. [9][10][11] Table II shows a summary of slurry characteristics and Table III shows various Cu slurry performances (Slurry A, B, and C) for low, middle, and high-speed Cu removal rates. First of all, the friction for the Cu reaction layers of those slurries is measured using a conventional friction force microscope (FFM), revealing that the friction of high-speed slurry is not the highest of all the slurries.…”
Section: Resultsmentioning
confidence: 99%
“…8) There is much research on the correlation between the removal rate and friction during polishing, which indicates removal rate increases with increasing friction. [9][10][11] However, since it is considered that friction generates heat, temperature may increase the removal rate. 12,13) On the other hand, chemical components in polishing slurry may change the property of the Cu reaction layer to be removed, suggesting that hydrophobicity of the Cu reaction layer in slurry solution affects the frictional property.…”
Section: Introductionmentioning
confidence: 99%
“…cold rolling) as proposed by Celis et al [13]. Dedy et al [25] [26] studied the behaviour of surface potentials of different metallic electrodes, scraped inside the solutions with different pH and described the phenomenon of an accelerated hydrogen evolution on freshly cleaved metallic surfaces in aqueous medium; it has been widely reported since then in the literature. For example, Burstein and Kearns [27] did an excellent study on describing an accelerated evolution of hydrogen from freshly generated surfaces of Cr, Fe and their alloys.…”
Section: Thermodynamicsmentioning
confidence: 99%
“…It has been reported that the removal mechanisms and surface quality in copper ECMP are affected by the applied potentials and pH values of electrolytes. [6][7][8] We have recently revealed that the mechanism of material removal in Ta ECMP is a synergy between formation and removal of Ta oxide. 9 Furthermore, it was found that there were different types of Ta oxides on the surface after ECMP.…”
Section: Introductionmentioning
confidence: 99%